Functional dynamics of G protein-coupled receptors reveal new routes for drug discovery - Conflitti, Paolo; Lyman, Edward; Sansom, Mark S. P.; Hildebrand, Peter W.; Gutiérrez-de-Terán, Hugo; Carloni, Paolo; Ansell, T. Bertie; Yuan, Shuguang; Barth, Patrick; Robinson, Anne S.; Tate, Christopher G.; Gloriam, David; et al. (Nature reviews. Drug discovery, 2025)
G protein-coupled receptors (GPCRs) are the largest human membrane protein family that transduce extracellular signals into cellular responses. They are major pharmacological targets, with approximately 26% of marketed drugs targeting GPCRs, primarily at their orthosteric binding site. Despite their prominence, predicting the pharmacological effects of novel GPCR-targeting drugs remains challenging due to the complex functional dynamics of these receptors. Recent advances in X-ray crystallography, cryo-electron microscopy, spectroscopic techniques and molecular simulations have enhanced our understanding of receptor conformational dynamics and ligand interactions with GPCRs. These developments have revealed novel ligand-binding modes, mechanisms of action and druggable pockets. In this Review, we highlight such aspects for recently discovered small-molecule drugs and drug candidates targeting GPCRs, focusing on three categories: allosteric modulators, biased ligands, and bivalent and bitopic compounds. Although studies so far have largely been retrospective, integrating structural data on ligand-induced receptor functional dynamics into the drug discovery pipeline has the potential to guide the identification of drug candidates with specific abilities to modulate GPCR interactions with intracellular effector proteins such as G proteins and β-arrestins, enabling more tailored selectivity and efficacy profiles. Recent advances in structural biology techniques and computational simulations have enhanced our understanding of the conformational dynamics of G protein-coupled receptors and their interactions with ligands. This Review highlights how such advances may be used in the discovery and optimization of drugs that target G protein-coupled receptors, focusing on three categories: allosteric modulators, biased ligands, and bivalent and bitopic compounds.